2017
DOI: 10.1016/j.cnsns.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Snaking bifurcations in a self-excited oscillator chain with cyclic symmetry

Abstract: Snaking bifurcations in a chain of mechanical oscillators are studied. The individual oscillators are weakly nonlinear and subject to self-excitation and subcritical Hopf-bifurcations with some parameter ranges yielding bistability. When the oscillators are coupled to their neighbours, snaking bifurcations result, corresponding to localised vibration states. The snaking patterns do seem to be more complex than in previously studied continuous systems, comprising a plethora of isolated branches and also a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Here, perhaps with an eye to the classical Stribeck curve, for the MB model we propose an exponentially weakening and linearly strengthening friction law. We show that this friction model yields to bistability thus vibration localization phenomena are expected as in Papangelo et al [24] if those oscillators were coupled together.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Here, perhaps with an eye to the classical Stribeck curve, for the MB model we propose an exponentially weakening and linearly strengthening friction law. We show that this friction model yields to bistability thus vibration localization phenomena are expected as in Papangelo et al [24] if those oscillators were coupled together.…”
Section: Introductionmentioning
confidence: 76%
“…Recently, Papangelo et al [24] have found localized vibration states in a self-excited chain of mechanical oscillators weakly elastically coupled, which lead to the so-called snaking bifurcations in the bifurcation diagram. A key feature of the system was that, if isolated from the structure, each nonlinear oscillator experiences a subcritical Hopf bifurcation in a certain range of the control parameter (yielding bistability 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…qualitative changes in system dynamics (see e.g. [19][20][21][22][23][24][25][26][27][28]). Nonlinear localization has been shown to appear not only in conservative systems [19] but also in friction-excited chains of weakly coupled oscillators [20,21], where the authors showed that the localization phenomenon is strongly related to the bistable behaviour of the single oscillator in the chain.…”
Section: Introductionmentioning
confidence: 99%
“…We refer interested readers to Papangelo et al [29] for detailed deductions. Lumped models in [29,30] illustrates a bistable zone where steady sliding and stick-slip limit cycle coexists in a certain range of the control parameter.…”
Section: X)mentioning
confidence: 99%